Analysis of the Degree of Acceptance of Illness Among Patients After a Stroke: An Observational Study - Guzek Z (Dove Medical Press, 2020)
Zbigniew Guzek,1 Joanna Kowalska2 1Department of Neurological Rehabilitation, University Hospital in Zielona Góra, Zielona Góra, Poland; 2Department of Physiotherapy, University School of Physical Education, Wroclaw, PolandCorrespondence: Joanna Kowalska Department of PhysiotherapyUniversity School of Physical Education, Paderewskiego 35 Street, Wrocław 51-612, PolandTel +48 71 347-35-22Fax +48 71 347-30-81Email joanna.kowalska@awf.wroc.plIntroduction: The aim of this study was to analyse the level of illness and disability acceptance in stroke patients undergoing regular rehabilitation at two time points, before rehabilitation and after 3 weeks, and to answer the following questions: What is the functional and emotional status of stroke patients, characterized by a lower and higher level of illness acceptance before and after the 3-week rehabilitation period? What factors, including clinical, sociodemographic, functional and emotional, are associated with the degree of illness acceptance in patients who have suffered a first stroke?Sample and Methods: The study included 64 patients after first stroke, aged 50– 87 years. The following tests were used: Acceptance of Illness Scale, Geriatric Depression Scale, Rivermead Mobility Index and Barthel Index. Tests were conducted at two time points, the first before rehabilitation and the second after 3 weeks of regular rehabilitation.Results: The study group had an average level of acceptance of their illness and disability, both before and after 3 weeks of rehabilitation. After rehabilitation process, statistically significant improvements were achieved in acceptance of illness, mood disorders, functional status, mobility and locomotion. Low levels of illness acceptance were observed in stroke patients with a poorer functional condition, with mood disorders, with primary and vocational education.Conclusion: The results suggest that the level of illness acceptance may be an important factor in the rehabilitation of stroke patients; however, further studies are necessary.Keywords: stroke, older adults, rehabilitation, acceptance of illness, symptoms of depression, functional status